Modifikasi Ducted Fan untuk Kebutuhan Pengarah Aliran Semprotan Pupuk Cair - Afabek, Randa; Nurdin, Hendri (Lembaga Yasin AlSys, 2024)
The use of agricultural drones has now experienced significant development. However, in its use it is often considered less effective because the liquid fertilizer sprayed through the nozzle tip is not on target. Then we need an additional tool in the form of a ducted fan which can increase the speed of the flow of fertilizer sprayed through the nozzle. This study uses a modification and reconstruction method of the ducted fan model that is already on the market so that it can be used as a flow guide. The modifications made are in the form of adding a cone with a size according to the hub and a height of 5 mm and a stator which is almost the same size as the fan which is around 65 mm and has the reverse direction, namely counter clock wise which functions as a flow guide. The results of the CFD research that has been carried out can be seen that the flow velocity at the outlet is 5.38394 m/s and the width of the flow which was originally 0.113791 m became 0.021235 m. Based on the results of the study it can be concluded that the fluid flow passing through the ducted fan looks smaller and directional so that it is in accordance with the purpose of the modifications that have been made and the flow speed increases so that the flow does not fly with the wind.